The use of dermatoscopy in Veterinary Medicine: A systematic literature review (Research, Society and Development, 2021)
Dermoscopy is a non-invasive diagnostic method performed in vivo, is quick, painless and does not harm the skin. It is used as a complementary exam and allows the observation of structures of the epidermis, the dermoepidermal junction and the superficial papillary and reticular dermis, being considered a link between the clinical picture (macroscopic) and the histopathological exam. In order to conduct a systematic review of articles published with dermoscopy in animals, through a literature review of the concepts, techniques and applications of this examination in Veterinary Medicine, an electronic search was carried out using the databases PubMed, Scielo, CAFe, Wiley online library and Google scholar. Twelve articles were found, 5 (41,66%) about canines, 4 (33,33%) about felines and 3 (25%) about horses. These studies used dermoscopy in the evaluation of normal feline and equine skin, feline and canine dermatophytosis, pattern of alopecia in dogs, acral congenital superficial dermal lymphatic malformations in cats and description of colorimetric pattern in dogs with erythroderma. Through this research, it was demonstrated that Dermatoscopy is still incipient in Veterinary Medicine, but with promising results. The dermoscopic examination proved to be useful to describe normal skin, as a screening and to aid in the conclusion of the diagnosis of some skin diseases in animals. Although researchers are interested in the subject, and the exam's potential, it is still necessary to carry out more research to identify new applicability of dermoscopy and dermoscopic patterns among the different skin diseases that affect animals.